(untitled) (Boston, 1991)
991 Harvard Business Review hardcover, Cynthia A. Montgomery (Editor, Introduction), Michael E. Porter (Editor, Introduction). For many companies, large and small, the question of formulating a competitive strategy is no longer one of choice. Their markets team with domestic and foreign competitors, their product and service life cycles are being dramatically compressed, and their customers' demands and expectations are escalating to new levels. Relying on intuition and seat-of-the-pants planning is the business equivalent of flying blind.
Keywords: Strategic planning,Lập kế hoạch chiến lược